Mutation and chaos in nonlinear models of heredity - Ganikhodjaev, Nasir; Saburov, Mansoor; Nawi, Ashraf Mohamed (Hindawi Publishing Corporation, 2014)
We shall explore a nonlinear discrete dynamical system that naturally occurs in population systems to describe a transmission of a trait from parents to their offspring. We consider a Mendelian inheritance for a single gene with three alleles and assume that to form a new generation, each gene has a possibility to mutate, that is, to change into a gene of the other kind. We investigate the derived models and observe chaotic behaviors of such models.